2015
DOI: 10.1039/c5ra12461a
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pesticide residues on fruit surfaces using laser induced breakdown spectroscopy

Abstract: The detection of chlorpyrifos residue on the surface of apples by laser induced breakdown spectroscopy (LIBS) was explored, establishing a new method for the fast detection of pesticide residues on fruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
2
11
0
4
Order By: Relevance
“…S is commonly found in fruit and vegetables, so it is best to measure P and Cl to allow the chlorpyrifos concentration to be determined. The LIBS spectrum of P has spectral features at 213.62, 214.91, 253.56, and 255.33 nm 27,30 . The LIBS spectrum of Cl has a characteristic peak at 837.59 nm 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S is commonly found in fruit and vegetables, so it is best to measure P and Cl to allow the chlorpyrifos concentration to be determined. The LIBS spectrum of P has spectral features at 213.62, 214.91, 253.56, and 255.33 nm 27,30 . The LIBS spectrum of Cl has a characteristic peak at 837.59 nm 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Laser-induced breakdown spectroscopy (LIBS) has been used to determine pesticide and heavy metal residues because samples can be analysed in situ (i.e., samples do not need to be taken to a laboratory), because it is fast, and because inline analyses can be performed 2729 . Members of our research team have used LIBS to determine pesticide residues in fruit 30 . The results of that study indicated that LIBS can be used to determine harmful chemicals in fruit but with relatively high limits of detection (LoDs) inappropriate for quantitatively determining trace chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, these methods are difficult to use for mapping in-field and in vivo due to their complex structure. Most pesticides contain specific elements (e.g., P and S), which thus provides an opportunity for mapping the elements’ concentrations in plant tissues using LipsImag [30,42]. In this study, we used chlorpyrifos, which is a common pesticide in China, as an example and attempted to collect 3-dimentional images of its distribution in plant leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Another issue that must be considered is the detection limit of the LIBS method, which can reach ppm levels for solid analyses under conventional conditions [28]. Using a vacuum environment, buffered gases and a multi-pulse laser can enhance the LIBS detection sensitivity but lead to difficulties with in-field and in vivo measurements [27,28,30]. During the LIBS measurement process, the plasma spectrum contains spectral characteristics of atom, iron, and molecule fragments, but we only used the atomic spectral line in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation